How to improve IVF success rates and increase access to treatment: Back to basics or more technology? - Wells, D (2011)
The 20th World Congress on Fertility and Sterility, organized by the International Federation of Fertility Societies, was held on 12-16 September 2010 in Munich (Germany). As usual for this triennial meeting, there was a focus on education, and efforts were made to provide the scientists, physicians and embryologists attending with updates on the latest developments in the field of reproductive medicine. The meeting was arranged around 18 'trilogies, each composed of three lectures addressing key subjects. The topics covered were diverse, ranging from contraception and ethics to fertility preservation and stem cells. Overall, the meeting succeeded in providing an excellent overview of the current status of reproductive medicine and the challenges facing the field as we enter the second decade of the 21st Century. Providing a summary of all of the excellent presentations at the Congress is beyond the scope of a short article such as this. Instead, this article seeks to highlight emerging trends that became apparent during the course of the meeting. © 2011 Expert Reviews Ltd.